X^4+6x^3-x^2-2x-7=0 решить уравнение !

cooldown229 cooldown229    1   15.08.2019 21:30    0

Ответы
ДенисБратанюк ДенисБратанюк  04.10.2020 21:46
Попробуйте так:
x^{4} + 6x^{3} - x^{2} -2x-7=0x^{4}- x^{2} + 6x^{3} - 2x-7=0 \\ \\ x^{2} ( x^{2}-1)+2x(3x-1)-7=0 \\ \\ x(x-1)(x+1)(x+2)-7=0 \\ \\ x^{2} (x^{2}-1)+2x( 3x^{2}-1)-7=0 \\ \\ x^{2}( x^{2}-1)+x( 6x^{2} -2)-7=0

⇒⇒a=( x^{2}-1) \\ \\ b=( 6x^{2}-2) \\ \\ a x^{2} +bx+c=0 \\ \\ a= x^{2}-1 \\ \\ b= 6x^{2}-2 \\ \\ c=-7
Дальше попробуйте посчитать или через дискриминант или по теореме Виета...
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра